Global Climate Policy and Corresponding Activities on a City-Level - Maike Sippel (Hamburg Institute of International Economics (HWWA), 2004)
Cities are not affected by global climate policy and the Kyoto Protocol – however many of them engage in voluntary activities. This paper analyses how communities in general and especially the city of Hamburg can contribute to global climate protection in their citypartnerships according to the slogan ?think global, act local?. Possible activities are in the fields of awareness-raising, capacity-building, exchange of experiences and joint project implementation. A focus is layed on projects according to the Clean Development Mechanism of the Kyoto Protocol in north-south citypartnerships. There is a clear potential for reduction of transaction costs in this kind of projects due to the institutional links of the citypartnership. For Hamburg, CDM-potential is high in its partnership with Shanghai. Further possibilities for action are micro-projects with a strong development component in the partnership with Léon (Nicaragua), exchange of experience with the city of Chicago on its emission trading scheme and adaptation activities especially against sea-/riverlevel rise with the cities of Osaka, Dresden and Marseille.
Keywords: 330; CDM; Citypartnership; Climate policy; Hamburg; Kyoto Protocol; Transaction costs; Klimaschutz; Clean Development Mechanism; Gemeinde; Kooperation; Stadtökologie; Transaktionskosten; Hamburg; Welt